Prolog antycznej komedii w oczach Profesora Sylwestra Dworackiego (1937–2020) - Wesołowska, Elżbieta (Przestrzenie Teorii, 2020)
The article is an attempt to remember the recently deceased, eminent researcher, Prof. Dr. Sylwester Dworacki, based on his article on prologues in Menander’s ancient Greek comedy.